Phytoremediation Mechanism for Emerging Pollutants : A Review - Kristanti, Risky Ayu; Tirtalistyani, Rose; Tang, Yien Yu; Thao, Nguyen Thi Thanh; Kasongo, Joseph; Wijayanti, Yureana (Tropical Aquatic and Soil Pollution, 2023)
As a result of urbanization and industrialization, emerging pollutants have become a global concern due to contamination and their potential adverse effects on the ecosystem and human health. However, the characteristics and environmental fate of emerging pollutants remain unclear due to the limitations of current technologies. Emerging pollutants are predominantly released into the environment through anthropogenic activities and accumulate in water, soil, air, and dust. Despite their typically low concentrations in the environment, exposure to these pollutants can result in endocrine disruption and other health impacts on the human body, as well as oxidative stress in organisms. Phytoremediation is a green biotechnology that utilizes plants in association with microorganisms to mitigate pollutants in contaminated areas through various mechanisms. It represents a cost-effective and environmentally friendly approach, although its efficacy can be hindered by both the biological condition of plants and ecological factors. Moreover, phytoremediation generally requires a longer remediation timeframe compared to alternative technologies. The remediation of emerging pollutants aligns with the "green liver model" theory, which encompasses translocation, internal transformation and conjugation, and sequestration as classification categories. Presently, several challenges are being encountered in this field, including a lack of information regarding emerging pollutants and their metabolism in plants, the absence of a modeling framework and standardized monitoring practices, limitations in sampling and analysis technologies, as well as phytoremediation technologies. Therefore, further research is warranted to delve into the behavior of emerging pollutants and their interactions with plants, aiming to develop or enhance existing technologies. Additionally, the concept of phytomanagement should be considered, as it offers a sustainable approach to environmental remediation.